Biased signaling of the proton‐sensing receptor OGR1 by benzodiazepines. Issue 2 (4th January 2018) - Pera, Tonio; Deshpande, Deepak A.; Ippolito, Michael; Wang, Bin; Gavrila, Adelina; Michael, James V.; Nayak, Ajay P.; Tompkins, Eric; Farrell, Eleni; Kroeze, Wesley K.; Roth, Bryan L.; Panettieri, Reynold A.; et al.
Abstract : GPCRs have diverse signaling capabilities, based on their ability to assume various conformations. Moreover, it is now appreciated that certain ligands can promote distinct receptor conformations and thereby bias signaling toward a specific pathway to differentially affect cell function. The recently deorphanized G protein‐coupled receptor OGR1 [ovarian cancer G protein‐coupled receptor 1 ( GPR68 )] exhibits diverse signaling events when stimulated by reductions in extracellular pH. We recently demonstrated airway smooth muscle cells transduce multiple signaling events, reflecting a diverse capacity to couple to multiple G proteins. Moreover, we recently discovered that the benzodiazepine lorazepam, more commonly recognized as an agonist of the γ‐aminobutyric acid A(GABAA ) receptor, can function as an allosteric modulator of OGR1 and, similarly, can promote multiple signaling events. In this study, we demonstrated that different benzodiazepines exhibit a range of biases for OGR1, with sulazepam selectively activating the canonical Gs of the G protein signaling pathway, in heterologous expression systems, as well as in several primary cell types. These findings highlight the potential power of biased ligand pharmacology for manipulating receptor signaling qualitatively, to preferentially activate pathways that are therapeutically beneficial.—Pera, T., Deshpande, D. A., Ippolito, M., Wang, B., Gavrila, A., Michael, J. V., Nayak, A. P., Tompkins, E., Farrell, E., Kroeze, W. K., Roth, B. L., Panettieri, R. A. Jr., Benovic, J. L., An, S. S., Dulin, N. O., Penn, R. B. Biased signaling of the proton‐sensing receptor OGR1 by benzodiazepines. FASEB J. 32, 862–874 (2018). www.fasebj.org